Fra realismo e utopia della pace. Emmanuel Mounier e Martin Buber - Costanzo, Giovanna (Filosofia Morale/Moral Philosophy, 2023)
Putin’s Russia’s war against Ukraine has left the world in suspense with fear of a possible global and atomic conflict. Faced with the question of whether peace or atomic war, it is perhaps necessary to rediscover the profound meaning of the word “peace”, but to ask other questions: is there a reasonableness in the choice of sending arms or should we insist on a denial of weapons at the cost of a brutal end to war? And does peace contain in itself a utopian matrix or a healthy realism? If these are questions to which it is difficult to give a clear and exhaustive answer, they nevertheless push us to rediscover the wise reflections of thinkers who lived during the barbarism of totalitarianism, such as Emmanuel Mounier and Martin Buber. With the two philosophers it is possible to find the motivations for a realism or for a utopian vision of peace: different positions but if brought back into our daily life, they can re-question our faiths and promote concrete actions.